Ultrastructural analysis of kidney, liver and duodenum isolated from treated rats with Ginkgo Biloba extract and effects of this medicinal plant on the biodistribution of the padiopharmaceutical sodium pertechnetate - Silvana Ramos Farias Moreno; Jorge José de Carvalho; Ana Lúcia Nascimento; Adriano Arnobio; Beni Olej; Margareth de Oliveira Timóteo; Luiz Querino de Araújo Caldas; Mário Bernardo Filho (Brazilian Archives of Biology and Technology, 2008)
Ginkgo biloba extract (EGb) has been used to treat memory and concentration deficits, acts as platelet activating factor antagonism and prevents against damages caused by free radicals. EGb is a standardized extract that contains 24% flavonoids and 6% terpenoids. The aim of this work was to evaluate the possible influence of an EGb on the ultrastructure of some organs isolated from rats and on the biodistribution of sodium pertechnetate (99mTcO4Na). The animals were treated with EGb and after six days, received 99mTcO4Na. The organs were isolated and fixed for ultrastructural analysis. The results showed that EGb has modified the ultrastructure of kidney, liver and duodenum and altered the biodistribution of 99mTcO4Na (P<0.05). It is speculated that the substances present in the EGb could act directly or generate metabolites capable to promote changes on the biodistribution of 99mTcO4Na and on the morphology of organs at ultrastructural level. O extrato de Ginkgo Biloba extract (EGb) tem sido usado para tratar dificuldades de concentração, memória, age como antagonista do fator de ativação de plaquetas e previne contra danos causados por radicais livres. EGb é um extrato padronizado com 24% de flavonóides e 6% de lactonas terpênicas. O objetivo deste estudo foi avaliar o efeito de um EGb na ultraestrutura de alguns órgãos isolados de ratos e na biodistribuição do radiofármaco pertecnetato de sódio (99mTcO4Na). Os animais foram tratados com EGb e após 6 dias receberam 99mTcO4Na. Os órgãos foram isolados e a radioatividade determinada. Os tecidos foram fixados para microscopia eletrônica. Os resultados mostraram que EGb alterou a ultraestrutura do rim, figado e duodeno e modificou a biodistribuição do 99mTcO4Na. Sugerimos que substâncias presentes no EGb poderiam agir diretamente ou gerar metabólitos capazes de promover alterações na biodistribuição e na morfologia de órgãos em nível ultraestrutural.